Comparative Effects of Instrument-Assisted Soft Tissue Mobilization (Iastm) and Muscle Energy Technique (Met) on Post-Operative Elbow Stiffness - Nayab Gohar; Sidra Majeed; Seher, Zarnab; Areej Azeem; Fatima Nadir; Tooba Asif (Journal of Liaquat University of Medical & Health Sciences, 2025)
OBJECTIVE: This study aimed to compare the effectiveness of Muscle Energy Technique (MET) and Instrument-Assisted Soft Tissue Mobilization (IASTM) in reducing pain, improving range of motion (ROM), and enhancing function in individuals with post-operative elbow stiffness. METHODOLOGY: A registered randomized clinical trial with NCT06575855 was conducted with 28 participants aged 30 to 50 with post-operative elbow stiffness from proximal radius-ulna or distal humerus fractures. Participants were randomly assigned to receive either MET or IASTM interventions. Pain levels were measured using the Visual Analog Scale (VAS), functional status was assessed via the Disabilities of the Arm, Shoulder, and Hand (DASH) questionnaire, and ROM was evaluated. Statistical analyses included the Wilcoxon Signed Rank Test, Mann-Whitney U-test, and paired and unpaired t-tests. RESULTS: MET and IASTM significantly reduced pain and improved ROM and function (p < 0.05). The IASTM group showed more significant pain reduction at rest and during activity (p-values of 0.050 and 0.039, respectively). No significant differences were found between the groups for improvements in ROM (elbow flexion/extension and forearm supination/pronation) and DASH scores, indicating similar effectiveness in these areas. CONCLUSION: MET and IASTM effectively manage post-operative elbow stiffness, with IASTM demonstrating superior pain reduction. These findings suggest that IASTM may be more beneficial for pain management in post-operative elbow stiffness, while both techniques offer comparable benefits for ROM and functional improvement.